A comparison between the manner in which court will second-guess the exercise of a private contractual power, on the basis of public policy, and the manner in which court will second-guess the exercise of public power, on the basis of rationality - Du Plessis, James (Department of Commercial Law, 2021)
This thesis considers and compares the standards against which Courts in South Africa review the exercise of private contractual power, on the basis of public policy, and the standards against which Courts in South Africa review the exercise of public power on the basis on rationality. This thesis undertakes this task in four main parts. Firstly, this thesis outlines important theoretical distinctions between legal and nonlegal powers, and private and public legal powers. In this regard, it is argued that what distinguishes a legal power from a non-legal power is the ability of the exercise of a legal power to in and of itself change another person's legal situation. This differs from the exercise of a non-legal, or a "power of influence" which has natural, and no automatically legal consequences, and will only change another legal situation if other (natural) consequences come to bear first. In relation to the distinction between private and public powers, this thesis outlines the traditional justifications for the distinction drawn between private and public power. Drawing on Austin, this thesis proposes that a useful demarcation between public and private powers is that the latter, more peculiarly, regards persons determined specifically, while the former, more peculiarly, regards the public considered indeterminately. Secondly, this thesis unpacks and details the standard of rationality that a Court will hold the exercise of a public power to, and highlights how rationality in this respect is an objective standard that relates essentially to a power's objective and whether or not the exercise of that power is related to that objective. Thirdly, and drawing on the latest pronouncements of the Constitutional Court, this thesis details what public policy requires of the exercise of private contractual power and highlights how what it requires is a value laden and facts dependent inquiry. Fourthly, this thesis goes on to argue that the standard of public policy, to which exercises of private contractual power are held to, is a higher standard than the standard of rationality that the exercises of public power is held to. Furthermore, this thesis argues that while such a situation is justifiable, it may become unjustifiable should Courts begin to misconstrue the fundamental differences between a legal and non-legal, and private and public power. Finally, this thesis submits that another iv cornerstone of South Africa's contract law, namely, that of privity of contract, may be a useful tool that Courts can use to keep balanced, on what this thesis outlines is a tightrope, that Courts have to walk in both having to imbue South Africa's contract law with Constitutional values, while at the same time ensuring that the higher standard that private contractual power wielders are held to, does not become unjustifiable.